Peripheral artery disease and risk of adverse outcomes in heart failure with preserved ejection fraction. Issue 9 (26th April 2017) - Sandesara, Pratik B.; Hammadah, Muhammad; Samman‐Tahhan, Ayman; Kelli, Heval M.; O'Neal, Wesley T.
Abstract : Background: Peripheral artery disease (PAD) in heart failure with preserved ejection fraction (HFpEF) is associated with an increased mortality risk, but the risk of individual outcomes associated with PAD in this patient group is less clear. Hypothesis: PAD is associated with adverse outcomes in HFpEF, including hospitalization and specific cardiovascular outcomes. Methods: We examined the association between PAD and adverse outcomes in 3385 patients with HFpEF (mean age, 69 ± 9.6 years; 49% male; 89% white) from the Treatment of Preserved Cardiac Function Heart Failure With an Aldosterone Antagonist Trial (TOPCAT). Baseline PAD was identified by self‐reported history and medical‐record review. The following outcomes were adjudicated by a clinical endpoint committee: hospitalization, hospitalization for heart failure (HF), myocardial infarction, stroke, death, and cardiovascular death. Results: Over a median follow‐up of 3.4 years (interquartile range, 2.0–4.9 years), an increased risk for hospitalization (hazard ratio [HR]: 1.36, 95% confidence interval [CI]: 1.16‐1.60), myocardial infarction (HR: 1.69, 95% CI: 1.07‐2.67), death (HR: 1.56, 95% CI: 1.22‐1.99), and cardiovascular death (HR: 1.53, 95% CI: 1.12‐2.10) was observed for those with PAD compared with those without PAD. PAD was not associated with incident stroke. The association between PAD and hospitalization for HF was limited to participants with prior history of HF hospitalization (n = 2449; HR: 1.51, 95% CI: 1.09‐2.13). Conclusions: PAD increases the risk for adverse outcomes in HFpEF and is associated with HF rehospitalization. Practitioners should be aware of the inherent risk associated with PAD in HFpEF.